Deconstructing phallogocentrism in Shahrnush Parsipur’s Touba and the meaning of night: a psycho-feminist study - Joodaki, Abdol Hossein; Elyasi, Zeinab (Penerbit UKM, 2015)
Shahrnush Parsipur (1946) is a celebrated and courageous Iranian novelist. This study deals with her controversial, epic novel Touba and the Meaning of Night (1989). The novel is analyzed based on Lacanian theory of subject formation and Cixousian concept of ‘ecriture feminine. In this essay a psychoanalytic-feminist discourse is used to intervene between a phallogocentric discourse and a feminist discourse. The pivotal aims of the study are to deconstruct Lacan’s concept of phallogocentrism, to redefine the concept of womanhood and to reconstruct feminine identity. According to the French psychoanalyst, Jacque Lacan, it is language that ultimately structures our conscious and unconscious mind and our identity. He introduced a tripartite scheme of psychic development: imaginary, symbolic and real. The symbolic order and its accompanying concept of phallogocentrism is the main focus of this study. By deconstructing symbolic phallus as the transcendental signified which signifies everything including female identity, the researcher’s aim is to focus on the need for a female framework and a feminine discourse free from male assumptions in order to reconstruct feminine identity. Helene Cixous, in her essay The Laugh of Medusa (1975), introduces a particular kind of female writing and tries to reconstruct the women’s shattered, colonized and marginalized identities in order to deconstruct the dominant symbolic order and phallocentric discourse. The task of this studyis to deal with and to follow the trace of masculine ideology and discourse in women’s identity in the novel Touba and the Meaning of Night. The study also, inspired by Helene Cixous’sprophecy of women’s experience of writing in a male dominated atmosphere claims that through deconstruction and break down of phallogocentrism, female subjects are constructed and a new discourse for women is established based on which they can reconstruct and forge their new identities.